A Saint of Our Own : How the Quest for a Holy Hero Helped Catholics Become American - Cummings, Kathleen Sprows (Book collections on Project MUSE., 2019)
"What drove American Catholics in their long and arduous quest, full of twists and turns across more than a century, to win an American-born saint? The absence of American names in the canon of the saints left many feeling spiritually unmoored and disrespected - to be able to look at the same American scenes upon which a saint had gazed would be a joy and privilege, certainly. But believers also had another reason for cultivating homegrown holiness, contends Kathleen Sprows Cummings in this ... chronicle of saint-making in America, where canonization was about holiness but never only about holiness"--